Задача управления колебательной системой по результатам измерений - Точилин, П. А. (Видавництво Львівської політехніки, 2011)
The paper considers the problem of controlling an oscillating system with disturbances in the dynamics. The control uses incomplete information containing uncertainties. A numerical method for solving the problem is described. It is based on the use of the ellipsoidal calculus techniques.
Keywords: неопределенность; синтез управлений; эллипсоидальное исчисление